Effect of crocin on aged rat kidney through inhibition of oxidative stress and proinflammatory state. (9th June 2016) - Samarghandian, Saeed; Azimi‐Nezhad, Mohsen; Borji, Abasalt; Farkhondeh, Tahereh
Abstract : This study evaluated whether crocin, a bioactive component of saffron, has a protective effect on kidney through reducing the oxidative stress and inflammatory response in aged rats. In this study the changes in activities of antioxidant enzymes, lipid peroxidation, glutathione (GSH) levels and the expression of pro‐inflammatory cytokines in the serum and renal tissue were evaluated by ELISA and RT‐PCR, respectively. The middle and aged rats were given intraperitoneal injections of crocin (10, 20, 30 mg/kg/day) for 4 weeks. After 4 weeks, animals were anesthetized with diethyl ether. The kidney samples were taken for biochemical analysis. The results revealed the aging was associated with a significant decrease in the activities of antioxidant enzymes, and GSH content with increase in lipid peroxidation level in kidney of the aged rats ( p  < 0.001). The increased levels of serum renal functional parameter, oxidative parameters ( p  < 0.01) and also pro‐inflammatory cytokine levels were significantly reduced by crocin administration ( p  < 0.05). The aged rats exhibited a dysregulation of the oxidative stress, and inflammation in the kidneys, but crocin treatment significantly reduced the expression of the inflammatory genes. These results provide pivotal documentation that crocin has a renoprotective effects against the development of oxidative stress and inflammation in the kidney of old rats. Copyright © 2016 John Wiley & Sons, Ltd.